A novel ΔNp63-dependent immune mechanism improves prognosis of HPV-related head and neck cancer - Mourtada, Jana; Lony, Christelle; Nicol, Anaïs; De Azevedo, Justine; Bour, Cyril; Macabre, Christine; Roncarati, Patrick; Ledrappier, Sonia; Schultz, Philippe; Borel, Christian; Burgy, Mickaël; Wasylyk, Bohdan; et al. (Frontiers in Immunology, 2023)
Background: Deconvoluting the heterogenous prognosis of Human Papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OSCC) is crucial for enhancing patient care, given its rapidly increasing incidence in western countries and the adverse side effects of OSCC treatments. Methods: Transcriptomic data from HPV-positive OSCC samples were analyzed using unsupervised hierarchical clustering, and clinical relevance was evaluated using Kaplan-Meier analysis. HPV-positive OSCC cell line models were used in functional analyses and phenotypic assays to assess cell migration and invasion, response to cisplatin, and phagocytosis by macrophages in vitro. Results: We found, by transcriptomic analysis of HPV-positive OSCC samples, a ∆Np63 dependent molecular signature that is associated with patient prognosis. ∆Np63 was found to act as a tumor suppressor in HPV-positive OSCC at multiple levels. It inhibits cell migration and invasion, and favors response to chemotherapy. RNA-Seq analysis uncovered an unexpected regulation of genes, such as DKK3, which are involved in immune response-signalling pathways. In agreement with these observations, we found that ∆Np63 expression levels correlate with an enhanced anti-tumor immune environment in OSCC, and ∆Np63 promotes cancer cell phagocytosis by macrophages through a DKK3/NF-B-dependent pathway. Conclusion: Our findings are the first comprehensive identification of molecular mechanisms involved in the heterogeneous prognosis of HPV-positive OSCC, paving the way for much-needed biomarkers and targeted treatment.